COMBINATORIAL ANALYSIS OF A PERMUTATION SCHEME WITH THE GIVEN MINIMAL RANGLE OF THE SCHEME - Natalya Enatskaya (Transactions of the Karelian Research Centre of the Russian Academy of Sciences, 2016)
The direct enumeration of the outcomes by the graph method is fulfilled and their number and the probability of outcomes of the scheme in the general combination scheme are find, the problem of enumeration of outcomes of the scheme is solved and on this base the algorithme of their quick modelling is suggested.